Brain Encoding of Social Approach: Is it Associated With Spatial Ability? - Marrero, Hipólito; Gámez, Elena; Urrutia, Mabel; Beltrán, David; Diaz, Jose M.; Yagual, Sara N. (Frontiers in Behavioral Neuroscience, 2019)
Human brains encode approach in social relationships as cognitively relevant for adaptive behavior. In this study, using event-related potentials, we found that reading approach-social actions is likely to cause activation around the right anterior/middle superior temporal sulcus, a brain area particularly involved in processing action intentionality and social relationship. We consider that the human capacity for the mental rotation of figures could also be adaptive for social relationship at the service of planning interaction with other bodies in social encounters. Encoding of social approach and spatial ability would correlate if both capacities are aimed at achieving the adaptive goal of secure interactions with others. We found a strong correlation between brain activation in the right temporal brain region and spatial ability. Implications of these results for the psychological mechanisms involved in adaptive social behavior are discussed.